Individual Differences, Economic Stability, and Fear of Contagion as Risk Factors for PTSD Symptoms in the COVID-19 Emergency - Di Crosta, Adolfo; Palumbo, Rocco; Marchetti, Daniela; Ceccato, Irene; La Malva, Pasquale; Maiella, Roberta; Cipi, Mario; Roma, Paolo; Mammarella, Nicola; Verrocchio, Maria Cristina; Di Domenico, Alberto (Frontiers in Psychology, 2020)
On January 30th 2020, the World Health Organization (WHO) declared the COVID-19 pandemic a Public Health Emergency of International Concern (PHEIC). Italy has been one of the most affected countries in the world. To contain further spread of the virus, the Italian government has imposed an unprecedented long-period lockdown for the entire country. This dramatic scenario may have caused a strong psychological distress, with potential negative long-term mental health consequences. The aim of the present study is to report the prevalence of high psychological distress due to the COVID-19 pandemic on the general population, especially considering that this aspect is consistently associated with PTSD symptoms. Furthermore, the present study aims to identify the risk factors for high PTSD symptoms, including individual differences and subjective perception of both economic and psychological aspects. We administered an online survey to 1253 participants during the peak period of the contagion in Italy. A logistic regression on the Impact of Event Scale – Revised (IES-R) scores was used to test the risk factors that predict the possibility to develop PTSD symptoms due to the COVID-19 pandemic. Gender (female), lower perceived economic stability, higher neuroticism, and fear and consequences of contagion were predictors of high PTSD symptomatology. The results, highlighted in the present study, extend our understanding of the COVID-19 pandemic’s impact on the population’s mental health, by identifying individuals at high-risk of developing PTSD. This may help with the implementation of specific protocols to prevent the possibility of developing symptoms of PTSD in target populations.